Cultural landscape devastation as a consequence of poor Sustainable Urban Development practice Case study: Kostanjica, Boka Bay, Montenegro - KOSARA KUJUNDZIC; SLAVICA STAMATOVIC VUCKOVIC (Journal of Contemporary Urban Affairs, 2019)
Natural and Culturo-Historical Region of Kotor, Boka Bay, Montenegro, is well known for its exceptional beauty, evaluated by UNESCO. The unique universal value has been embodied in the cultural landscape: vernacular architecture harmonized with the cultivated terraced landscape on the slopes of high, rocky mountains. Kostanjica is an old settlement in Boka Bay, former fishermen village, recognized for valuable elements of the cultural landscape: chestnut tree and laurel forest, terraced gardens with arable land, fruit gardens, traditional architecture in stone: clusters of houses, piers and docks, pedestrian pathways, pavements, retaining walls, well-integrated in the autochthone Mediterranean vegetation. Since Montenegro has pronounced itself Ecological state in 1991, environmental protection has become the highest priority in all Sustainable Development agendas and policies. Furthermore, preservation of regional peculiarity and fostering distinctive identity of a place, is one of the crucial sustainable development goals. The ongoing development of tourist resort “Boka Gardens” in Kostanjica has revealed these harmful, unsustainable tendencies in Montenegro. On the grounds of investor’s urban planning and profit-driven architecture, the unique and valuable cultural landscape of Kostanjica has been devastated to the extent that Boka Bay’s UNESCO status has been jeopardized. The paper researches cause of this damaging phenomena, seeking for ways of overcoming profoundly harmful building practices, thus leading to a more efficient and sustainable urban development.